2015
DOI: 10.1089/dia.2015.0027
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Glycemic Management with a Computerized Workflow and Decision Support System for Hospitalized Patients with Type 2 Diabetes on Different Wards

Abstract: Background: This study investigated the efficacy, safety, and usability of standardized glycemic management by a computerized decision support system for non-critically ill hospitalized patients with type 2 diabetes on four different wards.Materials and Methods: In this open, noncontrolled intervention study, glycemic management of 99 patients with type 2 diabetes (62% acute admissions; 41 females; age, 67±11 years; hemoglobin A1c, 65±21 mmol/mol; body mass index, 30.4±6.5 kg/m2) on clinical wards (Cardiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 23 publications
(33 reference statements)
1
71
2
5
Order By: Relevance
“…Umpierrez et al reported 2.0% of values in the hypoglycaemic range (<3.9 mmol/L) during basal‐bolus therapy using insulin glargine U100 in surgical patients . In a previous study using GlucoTab‐guided basal‐bolus therapy in combination with insulin glargine U100 in 99 inpatients, only 1.5% of all BG measurements were less than 3.9 mmol/L . In the present study using insulin glargine U300 with an otherwise unchanged basal‐bolus algorithm, we showed even lower rates of hypoglycaemia (0.9% of all capillary BG measurements).…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Umpierrez et al reported 2.0% of values in the hypoglycaemic range (<3.9 mmol/L) during basal‐bolus therapy using insulin glargine U100 in surgical patients . In a previous study using GlucoTab‐guided basal‐bolus therapy in combination with insulin glargine U100 in 99 inpatients, only 1.5% of all BG measurements were less than 3.9 mmol/L . In the present study using insulin glargine U300 with an otherwise unchanged basal‐bolus algorithm, we showed even lower rates of hypoglycaemia (0.9% of all capillary BG measurements).…”
Section: Discussioncontrasting
confidence: 41%
“…As GlucoTab facilitates insulin titration without requiring expert user input in the course of the treatment, it can be speculated that such a device could contribute to safely establishing glycaemic control in other fields of medicine such as surgery or neurology where other diseases are the main focus and diabetes is considered an inconvenient comorbidity. In a previous study in which GlucoTab was used on different general wards including surgery, the high acceptance rate on the part of staff, accompanied by good glycaemic control, was demonstrated . Acceptance rates and the mean glucose values achieved exceeded those seen in internal medicine wards where physicians interfered more with therapy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…[113] With respect to CPOE-based interventions, most studies found improvements in rates of hyperglycemia with an overall average reduction in patient day-weighted mean blood glucose ranging from 10.8 to 15.6 mg/dl, with only one of the studies showing a significant increase in hypoglycemic events. [113] Since the publication of this meta-analysis, there have been several additional studies evaluating the impact of CPOEs on glycemic outcomes [112, 114, 115]. Most, but not all, of these studies showed similar reductions in hyperglycemia rates without worsening hypoglycemia.…”
Section: Evidence-based Intervention Programs Across the Population Hmentioning
confidence: 99%